(untitled) (SCIENCE TIME JOURNAL, 2026)
The article investigates how gender differences between English speakers and Karakalpak speakers affect their communication methods through a comparative study of literature. The analysis shows that both communities exhibit universal patterns of gendered communication which include women’s preference for cooperative conversation and men’s inclination to speak competitively but the specific ways these patterns appear depend on the cultural standards and social structures and linguistic features that exist in each community.